Anti-reduction nanometer BaTiO3-based X7R dielectric ceramic with high bias voltage stability and preparation method of anti-reduction nanometer BaTiO3-based X7R dielectric ceramic
By preparing anti-reduction nano-BaTiO3-based X7R dielectric ceramics with high bias voltage stability, the problem of insufficient DC bias stability of multilayer ceramic capacitors in high voltage and high frequency environments has been solved, and the stability and resistance of dielectric properties have been achieved. The improvement in reduction performance meets the stability requirements of high-performance electronic products.
Patent Information
- Application Number
- CN202411429908.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-21
AI Technical Summary
Existing multi-layer ceramic capacitors have problems with insufficient DC bias stability in high voltage and high frequency environments, especially in the application of base metal electrodes. The insulation of ceramic materials decreases when sintered under reduced atmosphere, making it difficult to meet high performance. Stability requirements for electronic products.
Using anti-reduction nano-BaTiO3-based X7R dielectric ceramics with high bias voltage stability, the preparation method includes weighing a specific proportion of BaTiO3, Dy2O3, MgO, Yb2O3, NiO, BaZrO3 and C aSiO3 raw materials are mixed and ball milled, dried and pre-fired, then BaTiO3, Co2O3 and MnO2 are added for secondary ball milling, and finally sintered in a reducing atmosphere to produce ceramics with excellent dielectric properties and insulation properties.
The stability of the performance of the agency performance under the wide temperature and high DC bias is realized. The changing rate of the dielectric constant is less than 5 %. It meets the requirements of the X7R index and has good anti -downside performance and low production costs.
Smart Images

Figure BDA0005083352840000091 
Figure HDA0005083352850000011 
Figure HDA0005083352850000012
Abstract
Description
Technical Field
[0001] The invention relates to an anti-reduction nano BaTiO3-based X7R dielectric ceramic with high bias stability and a preparation method thereof, and is mainly used in the technical field of dielectric materials of base metal electrode multilayer ceramic capacitors. Background Art
[0002] At present, multilayer ceramic capacitors (MLCCs) are common electronic components in electronic devices. In order to reduce their production costs, nickel electrodes are used to replace traditional precious metal electrodes, but the electrode layer and the dielectric layer are required to be co-fired in a reducing atmosphere. BaTiO3, as the main dielectric material in MLCC, loses its dielectric layer function due to reduced insulation when sintered in a reducing atmosphere. Therefore, to achieve base metallization (BME) of MLCC electrodes, it is necessary to prepare anti-reduction BaTiO3 ceramics.
[0003] Modern electronic products have increasing requirements for miniaturization, high performance and reliability. In order to achieve the miniaturization of MLCC, the particle size of the sintered ceramic material is required to reach the nanometer level. Although there are various designs to increase the capacitance, the capacitance of ferroelectric materials will still drop significantly when DC voltage is applied due to the existence of DC bias phenomenon. Therefore, in order to ensure the long-term reliability of the application, in addition to considering the rated capacitance, it is also necessary to consider the effect of DC bias on the components. Obviously, the dielectric materials with X7R characteristics commonly used in my country (meeting TCC≤±15% in the temperature range of -55~125℃) cannot meet the actual needs in high voltage environments. High-performance electronic products such as smartphones, tablets, electronic cars, and medical equipment have high requirements for the stability of MLCC to ensure long-term stable operation of the equipment. In the field of power electronics, MLCC is used in power management, power transmission and energy storage systems, and needs to be able to withstand high voltage and high frequency working conditions, and has more stringent requirements for bias stability. In electric vehicles, grid optimization, and renewable energy power generation systems, the application of MLCC in filtering, noise reduction, and capacitor components has increased, and excellent bias stability and reliability are required. Therefore, the research and development of domestic X7R ceramic materials with high bias stability and anti-reduction properties suitable for base metal electrodes is of great significance to make up for the technical deficiencies of BME-MLCC ceramic materials in my country. Summary of the invention
[0004] In view of the shortcomings of domestic anti-reduction porcelain materials suitable for base metal electrodes, the present invention provides an anti-reduction nano-BaTiO3-based X7R dielectric ceramic with high bias stability and a preparation method thereof, which has good dielectric and insulating properties, and stable dielectric properties within a wide temperature range and under high DC bias. The band content change rate is less than 5% under a DC bias of 2V / μm, so as to solve the problems existing in the prior art proposed in the above background technology.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A method for preparing a reduction-resistant nano-BaTiO3-based X7R dielectric ceramic with high bias stability comprises the following steps:
[0007] (1) Weighing raw materials BaTiO3, Dy2O3, MgO, Yb2O3, NiO, BaZrO3 and CaSiO3; wherein, based on the mass of BaTiO3, the masses of Dy2O3, BaZrO3 and CaSiO3 are 0.5-5% of that of BaTiO3, and the masses of MgO, Yb2O3 and NiO are 0-2% of that of BaTiO3; the purity of the raw materials is greater than 99%;
[0008] (2) mixing and ball-milling, drying, and pre-calcining the raw materials weighed in step (1) to obtain ceramic powder A;
[0009] (3) adding BaTiO3, Co2O3 and MnO2 (the purity of these raw materials is also greater than 99%) to the ceramic powder A obtained in step (2), performing secondary ball milling and drying to obtain ceramic powder B; in this step, the mass of the added BaTiO3, Co2O3 and MnO2 accounts for 0.5-5%, 0-2% and 0-2% of the ceramic powder A, respectively;
[0010] (4) grinding the ceramic powder B obtained in step (3), mixing it with a binder, granulating and screening it, and dry pressing it to obtain a ceramic green body;
[0011] (5) The ceramic green body obtained in step (4) is kept at 500-700° C. in air for 1.5-3 hours to debind, and then sintered at 1150-1250° C. in a reducing atmosphere for 1-3 hours to obtain a reduction-resistant nano-BaTiO3-based bias-stabilized X7R dielectric ceramic.
[0012] Further preferably, in step (1), all raw materials are powders, the particle size of BaTiO3 powder is less than 150nm, and the particle sizes of the remaining raw materials are less than 300nm.
[0013] According to the above scheme, in step (2), the pre-firing temperature is 800-1100°C and the temperature is kept for 2-3 hours.
[0014] Further preferably, the ball milling in step (2) and step (3) is performed using zirconium oxide balls and anhydrous ethanol as the medium, and the ball milling is performed in a nylon planetary ball mill for 3 to 6 hours at a rotation speed of 300 to 500 r / min; the drying in step (2) and step (3) is performed in an oven at 90 to 110° C. for 12 to 24 hours.
[0015] Further preferably, in step (5), the binder is a polyvinyl alcohol aqueous solution with a concentration of 4 to 5 wt%, and the amount added is 4 to 8% of the mass of the ceramic powder B; the screening is through a 80 to 120 mesh sieve, and the dry pressing pressure is 150 to 200 MPa.
[0016] Further preferably, in step (5), the binder is discharged by heating the temperature to 500-700° C. at a heating rate of 0.5-1.5° C. / min and maintaining the temperature for 1-3 hours to discharge the binder.
[0017] According to the above scheme, in step (5), the sintering process is: heating to 950-1050°C at a heating rate of 3-5°C / min, then heating to 1150-1250°C at a heating rate of 1.5-2.5°C / min and keeping warm for 1-3 hours, then cooling to 950-1050°C at a cooling rate of 1.5-2.5°C / min, and finally cooling naturally with the furnace.
[0018] According to the above scheme, in step (5), the reducing atmosphere is composed of hydrogen and inert gas, or the reducing atmosphere is composed of hydrogen and nitrogen; wherein hydrogen accounts for 0.4-0.6% of the total volume of the reducing atmosphere.
[0019] The anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared by the above method has a pure perovskite structure, no second phase, high crystallinity, a room temperature dielectric constant of 1500-1700, a room temperature dielectric loss of less than 0.01, an average grain size of 100-150nm, and a room temperature resistivity of 10 10 ~10 12 Ω·cm, the dielectric constant change rate is within 4% to 8% under a DC bias of 2V / μm, and the temperature change rate does not exceed ±15% in the temperature range of -55 to 125℃, meeting the X7R index requirements.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The dielectric ceramics of the present invention have good dielectric properties. Since BaTiO3 with a particle size of less than 150nm is used as the main raw material, it is difficult to achieve X7R due to the limitation of particle size. The present invention achieves the broadening of the dielectric temperature curve by adding the main raw materials BaTiO3, Co2O3 and MnO2 again during the two mixings. The temperature change rate does not exceed ±15% in the temperature range of -55 to 125°C, the room temperature dielectric constant is 1500 to 1700, and the room temperature dielectric loss is less than 0.01, which meets the X7R index requirements. Moreover, the dielectric ceramics of the present invention use BaTiO3 powder with a particle size of less than 150nm as the main raw material, and the addition of CaSiO3 sintering aid greatly reduces the sintering temperature of the ceramics. The ceramics are sintered densely at 150 to 200°C, which is lower than the sintering temperature of pure barium titanate. The lower sintering temperature further reduces the grain size, and the average grain size of the ceramics finally obtained is 100 to 150nm.
[0022] 2. The dielectric ceramic of the present invention has good anti-reduction performance. By adding low-valent element acceptors such as MgO, NiO, Co2O3, MnO2, etc. to BaTiO3 and doping them into the B site, the generation of oxygen vacancies during sintering under a reducing atmosphere is greatly suppressed, the electron concentration in the ceramic is reduced, and a good insulation resistivity (10 10 ~10 12 Ω·cm); The dielectric ceramic of the present invention has good bias stability. The introduction of elements such as Dy2O3 and Yb2O3 greatly slows down the decrease of the dielectric constant of the ceramic under high voltage. The dielectric constant change rate is within 4% to 8% under a DC bias of 2V / μm.
[0023] 3. The current domestic technology does not have a formula that can achieve the above performance indicators at the same time, and the dielectric ceramics described in the present invention have low production costs, do not contain lead and volatile substances in the raw materials, and are green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM image of the 100nm BaTiO3 raw material used in the embodiment of the present invention.
[0025] Figure 2 The XRD spectrum of the anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared in Example 1;
[0026] Figure 3 The SEM image of the cross section of the anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared in Example 1;
[0027] Figure 4 The particle size distribution diagram of the cross section of the anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared in Example 1;
[0028] Figure 5 The graph of the dielectric constant of the anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared in Example 1 at different frequencies versus temperature (-55 to 200°C);
[0029] Figure 6 The graph of the capacitance-temperature change rate of the anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared in Example 1 at a frequency of 1 kHz versus temperature (-55 to 200°C);
[0030] Figure 7 The graph of the dielectric constant of the anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared in Example 1 as a function of DC bias at a frequency of 1 kHz (0-2 V / μm);
[0031] Figure 8 The graph of the dielectric constant of the anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared in Example 2 at different frequencies versus temperature (-55 to 200°C);
[0032] Fig. 9 The graph of the capacitance-temperature change rate of the anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared in Example 2 at a frequency of 1 kHz versus temperature (-55 to 200°C);
[0033] Fig.10 The graph of the dielectric constant of the anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared in Example 2 as a function of DC bias at a frequency of 1 kHz (0-2 V / μm);
[0034] Fig.11 The graph of the dielectric constant of the anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared in Example 3 at different frequencies versus temperature (-55 to 200°C);
[0035] Fig.12 The graph of the capacitance-temperature change rate of the anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared in Example 3 at a frequency of 1 kHz versus temperature (-55 to 200°C);
[0036] Fig.13 The graph of the dielectric constant of the anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared in Example 3 as a function of the DC bias at a frequency of 1 kHz (0-2 V / μm);
[0037] Fig.14 The graph of the dielectric constant of the dielectric ceramic prepared in Comparative Example 1 at different frequencies and temperatures (-55 to 200°C);
[0038] Fig.15 The graph of the dielectric constant of the dielectric ceramic prepared in Comparative Example 1 as a function of the DC bias voltage at a frequency of 1 kHz (0 to 2 V / μm);
[0039] Fig.16 The graph of the dielectric constant of the dielectric ceramic prepared in Comparative Example 2 at different frequencies and temperatures (-55 to 200°C);
[0040] Fig.17 This is a graph showing the change in dielectric constant of the dielectric ceramic prepared in Comparative Example 2 with DC bias at a frequency of 1 kHz (0 to 2 V / μm). DETAILED DESCRIPTION
[0041] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.
[0042] In the following embodiments, the purity of the raw materials involved, BaTiO3, Dy2O3, MgO, Yb2O3, NiO, BaZrO3, CaSiO3, Co2O3 and MnO2, is greater than 99%. All raw materials are powders. The particle size of the main material BaTiO3 powder is 100nm, and the particle sizes of the other raw materials are less than 300nm.
[0043] Example 1
[0044] A reduction-resistant nano-BaTiO3-based X7R dielectric ceramic with high bias stability, the preparation method of which specifically comprises the following steps:
[0045] (1) Taking the mass of BaTiO3 as 100%, weigh 1% Dy2O3, 0.3% MgO, 0.45% Yb2O3, and 1% CaSiO3 according to mass percentage;
[0046] (2) The raw materials weighed in step (1) are placed in a material tank, and are ball-milled on a planetary ball mill for 6 hours using zirconium oxide balls and anhydrous ethanol as the medium, at a speed of 387 r / min; then, the raw materials are dried at 100° C. for 24 hours, and then transferred to a muffle furnace for pre-calcination, and the pre-calcination is heated from room temperature to 1000° C. at a heating rate of 3° C. / min, and kept at this temperature for 2 hours, and then cooled with the furnace to obtain ceramic powder A;
[0047] (3) BaTiO3, Co2O3 and MnO2 are added to the ceramic powder A obtained in step (2) (the masses of BaTiO3, Co2O3 and MnO2 added here account for 2%, 0.85% and 0.5% of the ceramic powder A, respectively), and then the ceramic powder is placed in a material tank for secondary ball milling for 3 hours at a speed of 387 r / min, and dried in an oven at 100° C. to obtain ceramic powder B;
[0048] (4) Adding a 5 wt% polyvinyl alcohol aqueous solution to the ceramic powder B (Note: adding 0.1 ml of polyvinyl alcohol aqueous solution to 1 g of ceramic powder B), mixing well to form granules, passing through a 100-mesh sieve, aging for 24 h, and then dry-pressing it with a tablet press at a molding pressure of 150 MPa to obtain a ceramic green disc with a diameter of 12 mm and a thickness of about 1 mm;
[0049] (5) The ceramic disc green body obtained in step (4) is heated from room temperature to 600°C in a muffle furnace at a heating rate of 1°C / min and kept at this temperature for 2 hours, and naturally cooled in the furnace to discharge organic impurities in polyvinyl alcohol; then a reducing atmosphere is introduced into a tubular furnace (the reducing atmosphere is composed of hydrogen and nitrogen; wherein hydrogen accounts for 0.5% of the total volume of the reducing atmosphere), and the temperature is increased to 1000°C at a heating rate of 5°C / min, and then the temperature is increased to 1180°C at a heating rate of 2°C / min, and kept at this temperature for 2 hours, and then the temperature is decreased to 1000°C at a cooling rate of 2°C / min, and then naturally cooled in the furnace to obtain the above-mentioned anti-reduction nano-BaTiO3-based X7R dielectric ceramic with high bias stability.
[0050] The BaTiO3-based dielectric ceramic prepared in Example 1 was subjected to X-ray diffraction (XRD) testing. The XRD pattern is as follows: Figure 2 As shown, it can be seen that the ceramic sample is a pure phase perovskite structure of cubic phase without obvious second phase.
[0051] The BaTiO3-based dielectric ceramic prepared in Example 1 was broken into pieces and then a ceramic block of suitable shape was selected and thermally etched at 1100°C for 30 minutes in a reducing atmosphere. The thermally etched sample was then cleaned with anhydrous ethanol and dried, and its cross-sectional micromorphology was tested. Figure 3 As shown in Figure 2, the ceramic samples all show high crystallinity and no second phase; the particle size distribution of the ceramic cross section is shown in Figure 2. Figure 4 As shown, the grain size is mainly concentrated in the range of 100 to 150 nm, and the average grain size is 138 nm.
[0052] The insulation resistivity of the BaTiO3-based dielectric ceramic prepared in Example 1 was tested under a DC voltage of 1 V. As shown in Table 1, the insulation resistivity (25°C) at room temperature reached 1.1×10 11 Ω·cm.
[0053] The two sides of the BaTiO3-based dielectric ceramic prepared in Example 1 were ground and polished, and silver electrodes were coated. The dielectric properties of the BaTiO3-based dielectric ceramic were tested at frequencies of 100 Hz, 1 kHz, 10 kHz, 100 kHz, and 1 MHz. Figure 5As shown, the dielectric constant ε (25°C) at 1kHz room temperature is about 1518, and the dielectric loss tanδ (25°C) is about 0.0078; the temperature stability is as follows Figure 6 As shown, the temperature range of TCC ≤ ± 15% is -55 to 133°C.
[0054] The BaTiO3-based dielectric ceramic prepared in Example 1 was tested for bias stability. Figure 7 As shown, under a DC bias of 2 V / μm, the room temperature dielectric constant of the BaTiO3-based dielectric ceramic decreases from 1518 to 1443, and the change rate (Cap changeat 2 V / μm) is 4.94%.
[0055] Example 2
[0056] A reduction-resistant nano-BaTiO3-based X7R dielectric ceramic with high bias stability, the preparation method of which specifically comprises the following steps:
[0057] (1) Taking the mass of BaTiO3 as 100%, weigh 1% Dy2O3, 0.3% MgO, 0.45% Yb2O3, 2% BaZrO3, and 1% CaSiO3 according to mass percentage;
[0058] (2) Same as step (2) of Example 1;
[0059] (3) BaTiO3, Co2O3 and MnO2 are added to the ceramic powder A obtained in step (2) (the mass of the added BaTiO3 and Co2O3 accounts for 2% and 0.85% of the ceramic powder A, respectively), and then the mixture is placed in a material tank for secondary ball milling for 3 hours at a speed of 387 r / min, and dried in an oven at 100° C. to obtain ceramic powder B;
[0060] (4) Same as step (4) of Example 1;
[0061] (5) Same as step (5) of Example 1.
[0062] The insulation resistivity of the BaTiO3-based dielectric ceramic prepared in Example 2 was tested at a DC voltage of 1 V. As shown in Table 1, the insulation resistivity (25°C) at room temperature reached 1.4×10 11 Ω·cm.
[0063] The two sides of the BaTiO3-based dielectric ceramic prepared in Example 2 were ground and polished, and silver electrodes were coated. The dielectric properties of the BaTiO3-based dielectric ceramic were tested at frequencies of 100 Hz, 1 kHz, 10 kHz, 100 kHz, and 1 MHz. Figure 8As shown, the dielectric constant ε (25°C) at 1kHz room temperature is about 1644, and the dielectric loss tanδ (25°C) is about 0.0074; the temperature stability is as follows Fig. 9 As shown, the temperature range of TCC ≤ ± 15% is -55 to 130°C.
[0064] The BaTiO3-based dielectric ceramics prepared in Example 2 were tested for bias stability. Fig.10 As shown, under a DC bias of 2 V / μm, the room temperature dielectric constant of the BaTiO3-based dielectric ceramic decreases from 1644 to 1517, and the rate of change (Capchange at 2 V / μm) is 7.73%.
[0065] Example 3
[0066] A reduction-resistant nano-BaTiO3-based X7R dielectric ceramic with high bias stability, the preparation method of which specifically comprises the following steps:
[0067] (1) Taking the mass of BaTiO3 as 100%, weigh 1% Dy2O3, 0.3% MgO, 0.45% Yb2O3, 1% NiO, 2% BaZrO3, and 1% CaSiO3;
[0068] (2) Same as step (2) of Example 1;
[0069] (3) Same as step (3) of Example 1;
[0070] (4) Same as step (4) of Example 1;
[0071] (5) Same as step (5) of Example 1.
[0072] The insulation resistivity of the BaTiO3-based dielectric ceramic prepared in Example 3 was tested under a DC voltage of 1 V. As shown in Table 1, the insulation resistivity (Resistivity (25°C)) at room temperature reached 4.9×10 10 Ω·cm.
[0073] The two sides of the BaTiO3-based dielectric ceramic prepared in Example 3 were ground and polished, and silver electrodes were coated. The dielectric properties of the BaTiO3-based dielectric ceramic were tested at frequencies of 100 Hz, 1 kHz, 10 kHz, 100 kHz, and 1 MHz. Fig.11 As shown, the dielectric constant ε (25°C) at 1kHz room temperature is about 1602, and the dielectric loss tanδ (25°C) is about 0.0093; the temperature stability is as follows Fig.12 As shown, the temperature range of TCC ≤ ± 15% is -55 to 129°C.
[0074] The BaTiO3-based dielectric ceramic prepared in Example 3 was tested for bias stability. Fig.13 As shown, under a DC bias of 2 V / μm, the room temperature dielectric constant of the BaTiO3-based dielectric ceramic decreases from 1602 to 1500, and the rate of change (Capchange at 2 V / μm) is 6.36%.
[0075] Comparative Example 1
[0076] A BaTiO3 dielectric ceramic, the preparation method of which specifically comprises the following steps:
[0077] (1) The raw material is 100nm pure BaTiO3 ceramic powder;
[0078] (2) Same as step (4) of Example 1, omitting step (2) and step (3) of Example 1;
[0079] (3) The only difference from step (5) of Example 1 is that the sintering atmosphere is changed from the original atmosphere to air, the sintering temperature is changed from 1180°C to 1300°C, and the heating rate and holding time are consistent with those of Example 1.
[0080] The insulation resistivity of the BaTiO3 dielectric ceramic prepared in Comparative Example 1 was tested under a DC voltage of 1 V. As shown in Table 1, the insulation resistivity (Resistivity (25°C)) at room temperature reached 1.04×10 11 Ω·cm.
[0081] The two sides of the BaTiO3 dielectric ceramic prepared in Comparative Example 1 were ground and polished, and silver electrodes were coated. The dielectric properties of the BaTiO3 dielectric ceramic were tested at frequencies of 100 Hz, 1 kHz, 10 kHz, 100 kHz, and 1 MHz. Fig.14 As shown, the dielectric constant ε (25°C) is about 3031 and the dielectric loss tanδ (25°C) is about 0.015 at room temperature at 1kHz.
[0082] The BaTiO3 dielectric ceramic prepared in Comparative Example 1 was tested for bias stability. Fig.15 As shown, under a DC bias of 2 V / μm, the room temperature dielectric constant of the BaTiO3-based dielectric ceramic decreases from 3031 to 1197, and the change rate (Cap changeat 2 V / μm) is 60.51%.
[0083] Comparative Example 2
[0084] A BaTiO3-based dielectric ceramic, the preparation method of which specifically comprises the following steps:
[0085] (1) Same as step (1) of Example 1;
[0086] (2) Same as step (2) of Example 1;
[0087] (3) Same as step (4) of Example 1, omitting step (3) of Example 1;
[0088] (4) Same as step (5) in Example 1.
[0089] The insulation resistivity of the BaTiO3-based dielectric ceramic prepared in Comparative Example 2 was tested under a DC voltage of 1 V. As shown in Table 1, the insulation resistivity (25°C) at room temperature reached 1.04×10 10 Ω·cm.
[0090] The two sides of the BaTiO3 dielectric ceramic prepared in Comparative Example 2 were ground and polished, and silver electrodes were coated. The dielectric properties of the BaTiO3-based dielectric ceramic were tested at frequencies of 100 Hz, 1 kHz, 10 kHz, 100 kHz, and 1 MHz. Fig.16 As shown, the dielectric constant ε (25°C) is about 2094 and the dielectric loss tanδ (25°C) is about 0.017 at room temperature at 1kHz.
[0091] The BaTiO3 dielectric ceramic prepared in Comparative Example 2 was tested for bias stability. Fig.17 As shown, under a DC bias of 2 V / μm, the room temperature dielectric constant of the BaTiO3-based dielectric ceramic decreases from 2094 to 1784, and the change rate (Cap changeat 2 V / μm) is 14.8%.
[0092] Table 1 specifically lists the dielectric properties and insulation resistivity of the ceramics prepared in each embodiment at 1kHz.
[0093] Table 1
[0094]
[0095] Since the resistivity of pure BaTiO3 ceramic sintered in reducing atmosphere is less than 10 7 Ω·cm, it is impossible to test its DC bias performance, so pure BaTiO3 ceramic sintered in air (Comparative Example 1) is used as a blank control for reference. By doping with low-valent ions, the examples all obtain high resistivity (10 10 ~10 12Ω·cm), and has excellent anti-reduction performance. In Examples 1 to 3 of the present invention, BaTiO3 raw materials are added twice, and Co2O3 and MnO2 are added during the secondary mixing. This design can effectively widen the dielectric temperature curve and achieve the performance index of X7R. However, Comparative Example 2 does not perform this operation, and its temperature stability is poor. The dielectric constant change rate of Examples 1 to 3 under a DC bias of 2V / μm is significantly improved compared with the comparative example, all within 8%. In particular, Example 1 has the best bias stability, with a dielectric constant change rate of 4.94% under a DC bias of 2V / μm, and its comprehensive performance is the best.
[0096] In summary, the room temperature dielectric constant of the anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic of the present invention is 1500-1700, the room temperature dielectric loss is less than 0.01, the average grain size is 100-150nm, and the room temperature resistivity is 10 10 ~10 12 Ω·cm, the dielectric constant change rate is within 4% to 8% under a DC bias of 2V / μm, and the temperature change rate does not exceed ±15% in the temperature range of -55 to 125℃, meeting the X7R index requirements.
[0097] The above description is only an implementation mode of the present invention. It should be pointed out that for ordinary technicians in this field, various changes, modifications, substitutions and variations can be made to the embodiments without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a reduction-resistant nano-BaTiO3-based X7R dielectric ceramic with high bias stability, characterized in that: The following steps are involved: (1) BaTiO3, Dy2O3, MgO, Yb2O3, NiO, BaZrO3 and CaSiO3 are used as raw materials, and each raw material is weighed according to a proportion; wherein, based on the mass of BaTiO3, the mass of Dy2O3, BaZrO3 and CaSiO3 is 0.5-5% of that of BaTiO3, and the mass of MgO, Yb2O3 and NiO is 0-2% of that of BaTiO3; (2) mixing and ball-milling the raw materials weighed in step (1), drying and pre-calcining to obtain ceramic powder A; (3) adding BaTiO3, Co2O3 and MnO2 to the ceramic powder A obtained in step (2), performing secondary ball milling and drying to obtain ceramic powder B; in this step, the mass of the added BaTiO3, Co2O3 and MnO2 accounts for 0.5-5%, 0-2% and 0-2% of the ceramic powder A, respectively; (4) grinding the ceramic powder B obtained in step (3), mixing it with a binder, granulating and screening it, and dry pressing it to obtain a ceramic green body; (5) The ceramic green body obtained in step (4) is kept at 500-700° C. in air for 1.5-3 hours to debind, and then sintered at 1150-1250° C. in a reducing atmosphere for 1-3 hours to obtain a reduction-resistant nano-BaTiO3-based bias-stabilized X7R dielectric ceramic.
2. The method for preparing a reduction-resistant nano-BaTiO3-based X7R dielectric ceramic with high bias stability according to claim 1, characterized in that: In step (1), all raw materials are powders, the particle size of BaTiO3 powder is less than 150nm, and the particle sizes of the remaining raw materials are less than 300nm.
3. The method for preparing a reduction-resistant nano-BaTiO3-based X7R dielectric ceramic with high bias stability according to claim 1, characterized in that: In step (2), the pre-firing temperature is 800-1100° C. and the temperature is kept for 2-3 hours.
4. The method for preparing a reduction-resistant nano-BaTiO3-based X7R dielectric ceramic with high bias stability according to claim 1, characterized in that: The ball milling in step (2) and step (3) is performed by using zirconium oxide balls and anhydrous ethanol as the medium, placing the balls in a nylon planetary ball mill for 3 to 6 hours at a rotation speed of 300 to 500 r / min; the drying in step (2) and step (3) is performed by keeping the temperature in an oven at 90 to 110° C. for 12 to 24 hours.
5. The method for preparing a reduction-resistant nano-BaTiO3-based X7R dielectric ceramic with high bias stability according to claim 1, characterized in that: In step (5), the binder is a polyvinyl alcohol aqueous solution with a concentration of 4-5wt%, and the amount added is 4-8% of the mass of the ceramic powder B; the screening is through an 80-120 mesh sieve, and the dry pressing pressure is 150-200MPa.
6. The method for preparing a reduction-resistant nano-BaTiO3-based X7R dielectric ceramic with high bias stability according to claim 1, characterized in that: In step (5), the binder is discharged by heating the temperature to 500-700°C at a heating rate of 0.5-1.5°C / min and keeping the temperature for 1-3 hours to discharge the binder.
7. The method for preparing a reduction-resistant nano-BaTiO3-based X7R dielectric ceramic with high bias stability according to claim 1, characterized in that: In step (5), the sintering process is: heating to 950-1050°C at a heating rate of 3-5°C / min, then heating to 1150-1250°C at a heating rate of 1.5-2.5°C / min and keeping warm for 1-3 hours, then cooling to 950-1050°C at a cooling rate of 1.5-2.5°C / min, and finally cooling naturally with the furnace.
8. The method for preparing a reduction-resistant nano-BaTiO3-based X7R dielectric ceramic with high bias stability according to claim 1, characterized in that: In step (5), the reducing atmosphere is composed of hydrogen and inert gas, or the reducing atmosphere is composed of hydrogen and nitrogen; wherein the hydrogen accounts for 0.4-0.6% of the total volume of the reducing atmosphere.
9. The anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared by the method of claim 1, characterized in that: The dielectric ceramic has a pure perovskite structure and an average grain size of 100 to 150 nm.
10. The anti-reduction nano-BaTiO3-based bias-stabilized X7R dielectric ceramic prepared by the method of claim 1, characterized in that: The room temperature dielectric constant of dielectric ceramics is 1500-1700, the room temperature dielectric loss is less than 0.01, the average grain size is 100-150nm, and the room temperature resistivity is 10 10 ~10 12 Ω·cm, the dielectric constant change rate is within 4% to 8% under a DC bias of 2V / μm, and the temperature change rate does not exceed ±15% in the temperature range of -55 to 125℃, meeting the X7R index requirements.
Citation Information
Patent Citations
High-dielectric constant ceramic powder and ceramic capacitor produced therefrom and production method thereof
CN108585834A
Anti-reduction BaTiO3-based dielectric ceramic and preparation method thereof
CN110304916A
Low-cost, low-loss and temperature-super-stable dielectric material and preparation method thereof
CN116239378A
Low-loss, high-resistivity and anti-reduction BaTiO3-based dielectric ceramic and preparation method thereof
CN117125976A
Anti-reduction X7R type superfine ceramic material and preparation method thereof
CN117923892A